2012 IEEE International Conference on Robotics and Automation 2012
DOI: 10.1109/icra.2012.6225101
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end dexterous manipulation with deliberate interactive estimation

Abstract: Abstract-This paper presents a model based approach to autonomous dexterous manipulation, developed as part of the DARPA Autonomous Robotic Manipulation (ARM) program. The developed autonomy system uses robot, object, and environment models to identify and localize objects, and well as plan and execute required manipulation tasks. Deliberate interaction with objects and the environment increases system knowledge about the combined robot and environmental state, enabling high precision tasks such as key inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Recently this setting has received attention by teams participating in the DARPA ARM challenge [10]- [12] and the same study on humans when grasping without vision [13]. Those methods mostly depend on human expertise when designing the feedback controllers.…”
Section: Related Workmentioning
confidence: 98%
“…Recently this setting has received attention by teams participating in the DARPA ARM challenge [10]- [12] and the same study on humans when grasping without vision [13]. Those methods mostly depend on human expertise when designing the feedback controllers.…”
Section: Related Workmentioning
confidence: 98%
“…For objects with a known polygonal mesh model, experience databases can be built offline and serve as grasp look-up table once this object has been detected in the scene. In [19,13,8] it has been shown that in this case robust grasping and manipulation can be achieved by applying force control and exploiting constraints in the environment. However, to transfer successful grasps between different objects of which only partial and noisy information is known, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Each task was tested separately in static environments with only minor focus on obstacle avoidance but on grasping, sensor calibration and force feedback. Several teams have published their approaches [8], [9], [10]. In 2014, the EU-funded project EuRoC 1 [3] has been started.…”
Section: Introductionmentioning
confidence: 99%